Faktor yang Mempengaruhi Kejadian Stunting pada Baduta - Lani Febriani; Marthia Ikhlasiah; Priharyati Priharyati (Faletehan Health Journal, 2024)
This research aimed to identify the factors influencing stunting in children under two years in Bangendung Village, Cilegon Sub-district in 2023. The research method employed was a case control design with purposive sampling. The population of this study consisted of 54 mothers; 27 of them had stunted children under two years and 27 had non-stunted children under two years. The data collection used a questionnaire; the data analysis used chi-square test. The research results indicated that exclusive breastfeeding had a significant relationship with stunting in children under two years (p-value 0.003). Meanwhile, knowledge about exclusive breastfeeding, knowledge about complementary feeding, access to clean water, and family income do not have significant relationships with stunting in children under two years (with respective p-values of 1.000, 1.000, 0.726, and 1.000). Efforts by government and healthcare workers to educate the community, especially mothers, were carried out through the provision of information such as flyers, banners, and tutorial videos on proper exclusive breastfeeding and complementary feeding practices, disseminated in every integrated health post and auxiliary health center in Cilegon Subdistrict, Cilegon city.